Pregnancy outcome in patients with fibroid: a retrospective study - Dadhania, Bintu H.; Mehta, Shital T.; Yadava, Pushpa A.; Raval, Bina M.; Shah, Bhavi S.; Sisodiya, Viditsinh P.; Dadhania, Jay H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Fibroids are benign smooth muscle cell tumour of the uterus. In some patients of pregnancy associated with fibroid, it does not affect the outcome of pregnancy. On the other hand, various complications have been reported. The aim of our study was to evaluate the outcome in antenatal women with fibroids. Methods: This retrospective study was conducted at tertiary care center, obstetrics & gynecology department over a period of eighteen months between June 2018 to November 2019. Total 26 pregnant patients with >3 cm fibroid was included in the study. They were followed during antenatal period. Maternal age, parity, size of fibroid, complications during pregnancy, labour, and delivery, mode of delivery and indications of cesarean section were noted. Results: Out of 26 patients, 15 (57.6%) were between 26-30 years of age group and 16 (61.53%) were multigravidas. Normal vaginal delivery occurred in 8 (33.33%), while 16 (66.66%) delivered by caesarean section. There were 9 (34.61%) patients who had no complication whereas 17 (65.38%) had some complication. Pain was present in 8 (30.76%). PROM and preterm labour were present in 3 (18.75%) and 5 (19.23%) respectively. PPH was present in 2 (7.69%). Conclusions: Pregnant patients who have fibroids are to be carefully screened in the antenatal period, so as to have a regular follow up. The widespread use of ultrasonography has facilitated diagnosis and management of fibroids in pregnancy. The site and size of fibroid is very important to predict its effect on pregnancy.